PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN KERJA PEGAWAI PADA DINAS KOPERASI DAN UMKM KOTA TASIKMALAYA - Yusup Munawar Sholeh; Kusuma Agdhi Rahwana; Arga Sutrisna (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
The purpose of the study was to find out, firstly, the description of leadership, motivation, and work discipline of employees at the Dinas Koperasi dan UMKM Kota Tasikmalaya, secondly, the influence of leadership and motivation simultaneously on the work discipline of employees of the Tasikmalaya Dinas Koperasi dan UMKM Kota Tasikmalaya, and thirdly, the influence of leadership and motivation partially on the work discipline of the Dinas Koperasi dan UMKM Kota Tasikmalaya. The method used in this study is a quantitative method with a survey approach. The results showed that leadership was in the very good category, work motivation was in the good category, and work discipline for employees of the Dinas Koperasi dan UMKM Kota Tasikmalaya  was in the very good category. There is a significant simultaneous influence of leadership and work motivation on work discipline in the Dinas Koperasi dan UMKM Kota Tasikmalaya. There is a partial significant influence of leadership on work discipline in employees of the Dinas Koperasi dan UMKM Kota Tasikmalaya. There is a partial significant effect of work motivation on work discipline in employees of the Dinas Koperasi dan UMKM Kota Tasikmalaya.